Academic dishonesty among undergraduates: the role of neutralization attitude - Chan, Ling Meng; Othman, Jamilah; Omar, Zoharah; Alby, Jeffrey Lawrence D'Silva (Institute for Social Science Studies, Universiti Putra Malaysia, 2013)
Skyes & Matza (1957) proposed that individuals tend to use neutralization to motivate their decisions to engage in deviant behaviors. This indicated that even though students have strong motivations not to cheat may do so anyway after employing neutralizing strategies. Hence, this study attempted to examine the role of neutralization in influencing students’ attitude towards academic dishonesty. Students tended to use neutralization technique in order to free themselves from feeling guilty in engaging academic dishonesty. This study employed 620 randomly selected students from 6 different academic institutions. Results supported that students who engaged in academic dishonesty differ significantly from those who did not engaged in this deviant behavior with respect to their tendency to neutralize cheating. Results showed that cheating and neutralization were positively correlated among male and female. Hence, it showed that nowadays there are not differences in neutralization between male and female as their attitudes not longer different with respect to their achievement goals and expectations. Through the finding, it showed that the use of neutralization techniques explained why students acknowledged that cheating is wrong but still chooses to do it anyway.